Design and development of model-eliciting activity in energy and electrical power topics. Issue 3 (February 2019) - Festiana, I; Firman, H; Setiawan, A; Muslim, M
Abstract: The purpose of this research is to design and develop the model eliciting activity in the physics course on energy and electric power topic for students of electrical engineering. The method used in this research is Design and Development Research (DDR). This research was carried out in electrical engineering study program in one of private Universities in Lampung. This research consists of three phases of design and development research: 1) identify the problem, 2) describe the objectives, 3) design & develop the artifact. The result obtained in this research is the model eliciting activity design which consists of learning units based on model eliciting activity at the topic of energy and electric power to improve conceptual understanding students.